2019
DOI: 10.1002/kin.21247
|View full text |Cite
|
Sign up to set email alerts
|

SNAr reactions of substituted pyridines with secondary amines in aqueous solution: Kinetic and reactivity indices in density functional theory

Abstract: A kinetic study is reported for the reactions of 2-methoxy-3-nitropyridine 1a and 2methoxy-5-nitropyridine 1b with three secondary amines 2a-c (morpholine, piperidine, and pyrrolidine) in aqueous solution at 20 • C. The Brønsted-type plots are linear with nuc = 0.52 and 0.55 for pyridines 1a and 1b, respectively, indicating that the reaction proceeds through a S N Ar mechanism in which the first step is the ratedetermining step. Additional theoretical calculations using the DFT/B3LYP method confirm that the C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Ben Salah and coworkers 16 have shown that the experimental rate constants of the reactions of benzoselenadiazolium cation 18 with secondary amines (morpholine, piperidine, and pyrrolidine) in acetonitrile solution at 20 ° C are 30 to 56 orders of magnitude higher than those calculated from equation (1). Recently, Mahdhaoui and coworkers 45 investigated the reactivities of a series of pyridines 19 with anion of ethyl benzylacetate in DMSO at 20 °C solution and demonstrated that calculated rate constants according to the linear free energy relationship (equation 1) deviate by more than a factor 35 from those measured.…”
Section: Resultsmentioning
confidence: 99%
“…Ben Salah and coworkers 16 have shown that the experimental rate constants of the reactions of benzoselenadiazolium cation 18 with secondary amines (morpholine, piperidine, and pyrrolidine) in acetonitrile solution at 20 ° C are 30 to 56 orders of magnitude higher than those calculated from equation (1). Recently, Mahdhaoui and coworkers 45 investigated the reactivities of a series of pyridines 19 with anion of ethyl benzylacetate in DMSO at 20 °C solution and demonstrated that calculated rate constants according to the linear free energy relationship (equation 1) deviate by more than a factor 35 from those measured.…”
Section: Resultsmentioning
confidence: 99%
“…The E values are listed and compared in Figure 4 with those obtained in previous studies by our Laboratory for 2,5dinitrothiophene 5, [35] 4,6-dinitrotetrazolopyridine 6, [36] 2-methoxy-5-nitropyridine 7 [31] and 1,3,5-trinitrobenzene 8, [36] together with substrates 9-12 previously investigated by Mayr and coworkers. [37][38][39][40] Comparison of Figure 4 shows that the reactivity of nitrobenzoselenadiazol 1 b compares well with that of other neutral electrophiles such as the 2,5-dinitrothiophene 5 (E =-11.57) [35] and the 2-cinnamoyl-1-mesityl-3-methyl-1H-imidazol-3-ium 9 (E =-11.48), [37] while the reactivity of 1 a is similar to that of the benzaldehyde 10 (E =-12.90) [38] and (2-phenylethene-1,1-diylsulfonyl)dibenzene 11 (E =-12.93).…”
Section: Electrophilicity Parameters For 4-nitrobenzochalcogenadizolementioning
confidence: 88%
“…[37][38][39][40] Comparison of Figure 4 shows that the reactivity of nitrobenzoselenadiazol 1 b compares well with that of other neutral electrophiles such as the 2,5-dinitrothiophene 5 (E =-11.57) [35] and the 2-cinnamoyl-1-mesityl-3-methyl-1H-imidazol-3-ium 9 (E =-11.48), [37] while the reactivity of 1 a is similar to that of the benzaldehyde 10 (E =-12.90) [38] and (2-phenylethene-1,1-diylsulfonyl)dibenzene 11 (E =-12.93). [39] On the other hand, our electrophiles 1 appear to be much more electrophilic than 2-methoxy-5-nitropyridine 7, the least electrophilic species for which an E parameter has been determined to date [31] but, have an E value more than 6 units lower than that of 4,6-dinitrotetrazolopyridine 6 (E =-4.67) [36] and 4-nitrodiazonium ion 12 (E =-5.10), [40] compounds the general behaviour of which are representative of a superelectrophilic rankings. [19,23,25,41,42] Another interesting result is the finding that nitrobenzoselenadiazole 1 b is 2 orders of magnitude more electrophilic than 1,3,5-trinitrobenzene 8 (E =-13.19), [35] the common reference aromatic electrophile in σ-complexation processes.…”
Section: Electrophilicity Parameters For 4-nitrobenzochalcogenadizolementioning
confidence: 91%
See 2 more Smart Citations